Design of a WPT system for the powering of wireless sensor nodes: theoretical guidelines and experimental validation. Issue 1 (6th April 2016) - Donelli, M.; Rocca, P.; Viani, F.
Abstract : This work presents the design of a system for wireless power transmission based on a compact rectenna array able to supply low-power electronic devices such as wireless sensors. The receiving section is realized with an array of 12 rectangular patch antennas. Each elements of the array is connected with a suitable harmonic filter and a rectifying circuit by means of a coaxial feeding point. The transmitting section is realized with a one-dimensional prime focus parabolic reflector antenna, with a linear feeder composed by four dipole antennas. The rectenna array, the harmonic filter, the rectifying circuit of the receivers, and the transmitting section were optimized to reach the maximum operative range and efficiency, in term of power transfer. A system prototype has been designed, optimized, fabricated, and experimentally assessed. In particular, a prototype operating in the S band and able to provide a supply power of about 50 mW serves as proof-of-concept. Moreover, theoretical guidelines for the design of wireless power transmission are provided. The obtained experimental results are quite promising and demonstrated the capabilities of wireless power transmission systems as alternative power supply sources.